Dihedral evaluations of hypergeometric functions with the Kleinian projective monodromy. Issue 4 (3rd April 2019) - Vidunas, Raimundas
ABSTRACT: Algebraic hypergeometric functions can be compactly expressed as radical or dihedral functions on pull-back curves where the monodromy group is much simpler. This article considers the classical 3 F 2 -functions with the projective monodromy group PSL( 2, F 7 ) and their pull-back transformations of degree 21 that reduce the projective monodromy to the dihedral groupD 4 of 8 elements.